A screening study of the spatial distribution and cumulative toxicity of agricultural pesticides in the European Union’s waters - Pistocchi, A.; Dorati, C.; Galimberti, F.; Udias, A.; Bopp, S.; D’Andrimont, R.; Catarino, R.; Schaefer, R. B. (Frontiers in Environmental Science, 2023)
Pesticides can be an important stressor to aquatic ecosystems, and their use is strictly regulated in the European Union (EU). However, data on the use of pesticides are rather limited and poorly available, and monitoring is often insufficient to characterize their actual exposure and impact. The aim of the work presented here is to harness the limited data available and assess, for the first time, the distribution of concentrations and toxicity of 148 pesticide active substances (AS) for the whole EU. Starting from available estimates of pesticide use in agriculture and a simple screening-level model of their fate and transport, we quantify pesticide concentrations in soil and water. A comparison with monitoring data shows that predicted water concentrations are in plausible orders of magnitude, hence the model can be regarded as a first-approximation representation of the distribution of pesticides in the environment. The toxicity of individual pesticide active substances (AS) is characterized by their concentrations divided by the respective no observed effect concentrations (NOEC) for aquatic organisms, which represents the “toxic units” (TU) of each AS. The cumulative toxicity of pesticides in soils and streams of the EU is obtained by summing the TU of individual AS. We estimate that the toxicity of individual AS is generally well below 0.1 TU, indicating relatively safe environmental exposure. However, the cumulative toxicity of a mixture of AS can exceed 0.1 toxic units (TU) for more than 27% of the length of the EU’s stream network, and 1 TU for more than 4%. The cumulative toxicity at a given location is driven by only a handful of AS, but these differ from site to site reflecting the variability of pesticide use. Still, we estimate that only about 20 AS out of 148 appear among the top contributors to cumulative toxicity in most cases. While our assessment suggests a relatively widespread risk due to pesticide pollution, it also points to the important limitations concerning knowledge of pesticide use and monitoring of pesticide occurrence in the environment. These limitations need to be addressed in order to evaluate more accurately the effectiveness of EU pesticide policies. The assessment represents a proof-of-concept of a method that can be applied in support of the monitoring of pesticide policies implementation in the EU and elsewhere, once pesticide use can be estimated.